Use of hydrocolloid dressing in infants requiring open chest management after cardiac surgery - Shinya Yokoyama; Rei Tonomura; Ryohei Fukuba; Kazuhiro Mitani; Hideki Uemura (Surgical Case Reports)
Abstract Purpose Sternal splintage is known as an effective maneuver to stabilize hemodynamics during the immediate postoperative period, particularly in very sick infants. On the other hand, its wound management is not always straightforward. We employed dressing using a product made of a hydrocolloid material in such circumstances. This report describes our experience in utilizing the dressing in term of its potential advantages. Materials and methods Six infants needed open chest management following complicated procedures for congenital heart disease. A polytetrafluoroethylene patch was fixed to augment the skin defect at the time of sternal splintage, and a hydrocolloid dressing was applied to entirely cover the wound including the suture line. Result All patients survived their difficult circumstances. None of them suffered wound complications such as infection or healing problem during sternal splintage or subsequent to eventual chest closure. The dressing product was easy to handle with no adverse events associated with its material. Conclusions It is reconfirmed that a dressing made of hydrocolloid material was of practical use for sealing the wound in infants requiring open chest management after cardiac surgery.